2020
DOI: 10.1542/hpeds.2019-0230
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use for Inpatient Bronchiolitis: Did National Guidelines Impact Practice at a Pediatric Hospital?

Abstract: BACKGROUND AND OBJECTIVES: Bronchiolitis is a common lower respiratory tract infection that affects infants and young children. Because of variability in physician practice, inpatient management varies among pediatricians. In 2014, the Canadian Pediatric Society published national guidelines aimed at standardizing the inpatient management of this illness, which included recommending against the need for antibiotics for most patients. The study objective was to evaluate antibiotic prescription and supportive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…Considering only the patients without co-morbidity, the median (IQR) LOS was 3 (2-5) days. This LOS is comparable to 1.6-3.3 days reported from the western countries in which patients with comorbidities or admitted to the ICU were excluded (Lopez et al, 2020, Milner et al, 2018, Parikh et al, 2017, Walls et al, 2017. The shortest LOS of 1.6 days reported from Wall et al (Walls et al, 2017) is probably due to the inclusion criteria.…”
Section: Newman Et Al Reported 3gc Prescription Rates Before Launchisupporting
confidence: 74%
“…Considering only the patients without co-morbidity, the median (IQR) LOS was 3 (2-5) days. This LOS is comparable to 1.6-3.3 days reported from the western countries in which patients with comorbidities or admitted to the ICU were excluded (Lopez et al, 2020, Milner et al, 2018, Parikh et al, 2017, Walls et al, 2017. The shortest LOS of 1.6 days reported from Wall et al (Walls et al, 2017) is probably due to the inclusion criteria.…”
Section: Newman Et Al Reported 3gc Prescription Rates Before Launchisupporting
confidence: 74%
“…24 25 Antibiotic treatment is not recommended for acute bronchiolitis, 9 26 27 and overuse is a known problem. [28][29][30] Our results showed a very low use of antibiotics, consistently below 5%, compared with other countries, where rates in the range of 3.5%-11.1% are reported. 28 We found a steady rise in the use of highflow oxygen in the hospital setting.…”
Section: Open Accesssupporting
confidence: 40%
“…In a study carried out in Canada to analyze the use of antibiotics in bronchiolitis before and after the national GL publication, it was found that the rates of antibiotic initiation were almost equal over time (about 44%). However, more antibiotics were discontinued during hospitalization and fewer patients were discharged with antibiotics in the post-GL group, illustrating that antibiotic prescribing practices can change [41]. Analyzing the impact of national GL in children hospitalized with bronchiolitis in public Portuguese hospitals, Fontoura-Matias et al showed only a modest improvement in management, including antibiotic prescription, with significant variation between regions [42].…”
Section: Discussionmentioning
confidence: 99%